EPA and DHA differentially modulate monocyte inflammatory response in subjects with chronic inflammation in part via plasma specialized pro-resolving lipid mediators: A randomized, double-blind, crossover study - So, Jisun; Wu, Dayong; Lichtenstein, Alice H.; Tai, Albert K.; Matthan, Nirupa R.; Maddipati, Krishna Rao; Lamon-Fava, Stefania (Atherosclerosis, 2021)
The independent effects of eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) on chronic inflammation through their downstream lipid mediators, including the specialized pro-resolving lipid mediators (SPM), remain unstudied. Therefore, we compared the effects of EPA and DHA supplementation on monocyte inflammatory response and plasma polyunsaturated fatty acids (PUFA) SPM lipidome. After a 4-week lead-in phase (baseline), 9 men and 12 postmenopausal women (50–75 years) with chronic inflammation received two phases of 10-week supplementation with 3 g/day EPA and DHA in a random order, separated by a 10-week washout. Compared with baseline, EPA and DHA supplementation differently modulated LPS-stimulated monocyte cytokine expression. EPA lowered TNFA (p < 0.001) whereas DHA reduced TNFA (p < 0.001), IL6 (p < 0.02), MCP1 (p < 0.03), and IL10 (p < 0.01). DHA lowered IL10 expression relative to EPA (p = 0.03). Relative to baseline, EPA, but not DHA, decreased the ratios of TNFA/IL10 and MCP1/IL10 (both p < 0.01). EPA and DHA also significantly changed plasma PUFA SPM lipidome by replacing n-6 AA derivatives with their respective derivatives including 18-hydroxy-EPA (+5 fold by EPA) and 17- and 14-hydroxy-DHA (+3 folds by DHA). However, DHA showed a wider effect than EPA by also significantly increasing EPA derivatives and DPA-derived SPM at a greater expense of AA derivatives. Different groups of PUFA derivatives mediated the differential effects of EPA and DHA on monocyte cytokine expression. EPA and DHA had distinct effects on monocyte inflammatory response with a broader effect of DHA in attenuating pro-inflammatory cytokines. These differential effects were potentially mediated by different groups of PUFA derivatives, suggesting immunomodulatory activities of SPM and their intermediates. [Display omitted] •eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) differently modulate the ex vivo inflammatory response of human monocytes.•DHA affects a wider range of plasma polyunsaturated fatty acids (PUFA) pro-resolving lipid mediators (SPM) lipidome than EPA.•Different subgroups of PUFA derivatives mediate anti-inflammatory effects of EPA and DHA.